Transcriptome Profiling of Atlantic Salmon (Salmo salar) Parr With Higher and Lower Pathogen Loads Following Piscirickettsia salmonis Infection - Xue, Xi; Caballero-Solares, Albert; Hall, Jennifer R.; Umasuthan, Navaneethaiyer; Kumar, Surendra; Jakob, Eva; Skugor, Stanko; Hawes, Christopher; Santander, Javier; Taylor, Richard G.; Rise, Matthew L. (Frontiers in Immunology, 2021)
Salmonid rickettsial septicemia (SRS), caused by Piscirickettsia salmonis, is one of the most devastating diseases of salmonids. However, the transcriptomic responses of Atlantic salmon (Salmon salar) in freshwater to an EM-90-like isolate have not been explored. Here, we infected Atlantic salmon parr with an EM-90-like isolate and conducted time-course qPCR analyses of pathogen load and four biomarkers (campb, hampa, il8a, tlr5a) of innate immunity on the head kidney samples. Transcript expression of three of these genes (except hampa), as well as pathogen level, peaked at 21 days post-injection (DPI). Multivariate analyses of infected individuals at 21 DPI revealed two infection phenotypes [lower (L-SRS) and higher (H-SRS) infection level]. Five fish from each group (Control, L-SRS, and H-SRS) were selected for transcriptome profiling using a 44K salmonid microarray platform. We identified 1,636 and 3,076 differentially expressed probes (DEPs) in the L-SRS and H-SRS groups compared with the control group, respectively (FDR = 1%). Gene ontology term enrichment analyses of SRS-responsive genes revealed the activation of a large number of innate (e.g. “phagocytosis”, “defense response to bacterium”, “inflammatory response”) and adaptive (e.g. “regulation of T cell activation”, “antigen processing and presentation of exogenous antigen”) immune processes, while a small number of general physiological processes (e.g. “apoptotic process”, development and metabolism relevant) was enriched. Transcriptome results were confirmed by qPCR analyses of 42 microarray-identified transcripts. Furthermore, the comparison of individuals with differing levels of infection (H-SRS vs. L-SRS) generated insights into the biological processes possibly involved in disease resistance or susceptibility. This study demonstrated a low mortality (~30%) EM-90-like infection model and broadened the current understanding of molecular pathways underlying P. salmonis-triggered responses of Atlantic salmon, and identified biomarkers that may assist to diagnose and combat this pathogen.